Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] (Science of the Total Environment (2022) 813, (S0048969721074222), (10.1016/j.scitotenv.2021.152345)) - Ventura Fernandes, Bianca H.; Feitosa, Natália Martins; Barbosa, Ana Paula; Bomfim, Camila Gasque; Garnique, Anali M.B.; Rosa, Ivana F. [UNESP]; Rodrigues, Maira S. [UNESP]; Doretto, Lucas B. [UNESP]; Costa, Daniel F. [UNESP]; Camargo-dos-Santos, Bruno [UNESP]; Franco, Gabrielli A. [UNESP]; Neto, João Favero [UNESP]; et al. (Elsevier, 2024)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal). This article has been retracted at the request of the Editors-in-Chief. Post-publication, an investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team determined that 2 of the reviews for this manuscript were fictitious. 2 reviews were submitted under the name of known scientists without their knowledge. The name and fictitious contact details of the reviewers were submitted by the Corresponding Author Guilherme Malafaia during the manuscript submission process. Although the paper was reviewed by additional reviewers chosen by the Editor, this breach compromised the editorial process. The Editors-in-Chief have lost confidence in the validity/integrity of the article and its findings and have determined that it should be retracted.